Identifikasi Tingkat Kesegaran Daging Ayam Kampung Menggunakan Metode KNN Berdasarkan Warna Daging - Kasanova, Sinyo; Udjulawa, Daniel (Algoritme Jurnal Mahasiswa Teknik Informatika, 2024)
Free-range chicken is a type of poultry that is still natural in the sense that it has not received genetic improvement treatment. The economically advantageous characteristics of free-range chickens are relatively few compared to purebred chickens, even in terms of egg production and the ability to produce meat. Determining the level of freshness of free-range chicken meat is an important factor in determining the quality of the meat to be consumed, so that people as consumers can avoid the worst risks if they consume free-range chicken meat that is not fresh. For this reason, research was carried out to determine the level of freshness of free-range chicken meat using the KNN and HSV methods. The level of freshness is divided into 3 levels, namely rotten, fresh and not fresh. Based on the results of tests carried out using the KNN method with models k=1, k=3, k=5, k=7, k=9, and k=11, it was found that in the testing process the value of the highest accuracy was obtained by the value k=5 namely 80% and k=7, namely 80%, meanwhile the lowest result was obtained by the value k=1, namely 80%.